(untitled) (Revista Apotheke, 2025)
This article presents the results of an analysis of theses, dissertations and articles that address aesthetic education in the training of Visual Arts teachers in the South of Brazil, between 2014 and 2024. Through a qualitative analysis, the 12 publications found were organized into three thematic units: aesthetic experience and mediation in Visual Arts education; aesthetics as a critical practice; and aesthetics and curriculum in Visual Arts education. The study demonstrates that aesthetics, when understood as a sensitive and creative practice, constitutes a formative dimension, surpassing a technical or disciplinary approach. The main theoretical frameworks supporting the analyses are Vygotsky, Freire, and Zanella, who provide a foundation for understanding aesthetic education as a humanizing, poetic, and political dimension. The analysis reveals convergences and divergences in the investigative paths of the research reviewed, as well as possible articulations between subjectivity, educational policies, and artistic practices in Visual Arts teaching.